Uji Kondisi Optimum Desorpsi Anion Fosfat pada Silika Mesopori Termodifikasi DMA (Dimethylamine) - Hainunnisa Syafitriza; Budhi Oktavia; Hary Sanjaya; Hardeli Hardeli (Periodic, 2023)
Mesoporous silica is solid silica having a pore size of 2-50 nm. Silica modification is done to increase the ability of silica to absorb anions, one of which is phosphate anion. The modifier compound used is dimethylamine. Silica and dimethylamine can bind with the addition of a linking compound, namely GPTMS. This modified silica can be used to adsorb phosphate anions to see the absorption of silica against phosphate anions. Phosphate ion adsorption using silica has an adsorption capacity of 0.0172 mg/g with an absorption percentage of 88.09%. Desorption with hydrochloric acid obtained a desorbed phosphate concentration of 0.773 mg/L with a desorption percentage of 89.02% while using sulfuric acid the desorbed phosphate concentration was 0.437 mg/L with a desorption percentage of 48.81%. The concentration variations of hydrochloric acid were 0.010 M, 0.025 M, 0.050 M, 0.075 M, 0.10 M, 0.15 M and 0.20 M. The maximum desorption result at 0.1 M concentration was 0.0086 mg with a percentage of 100%.